35 Years on the Road from Research to Practice: A Review of Studies on Four Content Enhancement Routines for Inclusive Subject‐Area Classes, Part I. Issue 3 (12th July 2021) - Schumaker, Jean Bragg; Fisher, Joseph B.
Abstract: This article is the first part of a two‐part article focusing on the 35‐year journey of a team of researchers as they navigated the research‐to‐practice road related to the development of the Content Enhancement Routines, instructional routines to be used during inclusive subject‐area instruction. Part I tells the story of the first half of that journey and highlights the original validation research studies that were conducted on four Content Enhancement Routines: the Concept Mastery Routine, the Concept Comparison Routine, the Concept Anchoring Routine, and the Question Exploration Routine. Each study utilizes some type of experimental research design to determine the effects of teachers' use of the routine on the test performance of subgroups of secondary students within inclusive classes. The subgroups included students with disabilities and students without disabilities—high achievers, normal achievers, and low achievers. In all of the studies, the students who participated in the instructional routine earned significantly higher test scores than students who participated in a standard lecture/discussion lesson. Additionally, where significant differences were found, the performance of each subgroup of students that participated in the instructional routine was significantly higher than the performance of their paired subgroup that participated in the lecture/discussion lesson.